1998
DOI: 10.1063/1.120853
|View full text |Cite
|
Sign up to set email alerts
|

Pit formation in GaInN quantum wells

Abstract: The formation of pits in GaInN quantum wells (QWs) has been studied by atomic force microscopy and transmission electron microscopy. It is found that the pits have a hexahedron cone morphology with six sidewalls on 〈11̄01〉 planes and dislocations connected to their vertexes. The dislocations may induce the formation of pits during the growth of GaInN QWs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
168
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 252 publications
(182 citation statements)
references
References 9 publications
12
168
2
Order By: Relevance
“…For InGaN and GaN films V-shaped pinholes are commonly observed. 2,15 Pinholes are open hexagonal inverted pyramids defined by the six ͕10-11͖ planes, and are reported to originate from either threading dislocations, 15 stacking mismatch boundaries induced by stacking faults due to strain relaxation 16 or from slow growth rate on polar ͑10-11͒ planes induced by impurity poisoning of growth steps or any development of surface roughness during growth. 17 Liliental-Weber et al 17 have studied the formation of V-shape pinholes, related to V-shape facets in ͑10-11͒ polar planes and nanotubes with ͑10-10͒ facets, in tensile strained GaN films.…”
Section: Discussionmentioning
confidence: 99%
“…For InGaN and GaN films V-shaped pinholes are commonly observed. 2,15 Pinholes are open hexagonal inverted pyramids defined by the six ͕10-11͖ planes, and are reported to originate from either threading dislocations, 15 stacking mismatch boundaries induced by stacking faults due to strain relaxation 16 or from slow growth rate on polar ͑10-11͒ planes induced by impurity poisoning of growth steps or any development of surface roughness during growth. 17 Liliental-Weber et al 17 have studied the formation of V-shape pinholes, related to V-shape facets in ͑10-11͒ polar planes and nanotubes with ͑10-10͒ facets, in tensile strained GaN films.…”
Section: Discussionmentioning
confidence: 99%
“…7 Another suggested mechanism involves the formation of pits at the dislocation surface termination. 12 These topographical V-defects may induce a screening of the threading dislocations for carriers thanks to a potential barrier located in their vicinity. 13 Besides an improved structural quality, the InGaN UL has been proposed to affect the band profile due to pinning of the Fermi level at the InGaN/ GaN interface, which in turn reduces the built-in electric field in the QWs and thus leads to an increase in the QW radiative efficiency.…”
mentioning
confidence: 99%
“…10 Some researchers have observed that V-shape defects are connected to the TDs at their bottom. 16,17 To investigate the morphology of the InGaN/GaN MQWs structure grown on both planar and vicinal substrates, SEM images were employed. Fig.…”
mentioning
confidence: 99%